Hubungan antara Dukungan Sosial Rekan Kerja dan Kebersyukuran dengan Kepuasan Hidup pada Guru Honorer - Dian Suryani; Nugroho Arief Setiawan; Indah Dwi Cahya Izzati (SENTRI: Jurnal Riset Ilmiah, 2026)
Honorary teachers in Indonesia play a crucial role in education but face significant challenges, including low salaries, job insecurity, high workloads, and limited benefits, which often lead to psychological distress and reduced well-being. Employing a quantitative correlational approach, data were collected from 102 honorary junior high school teachers in Bandar Lampung using purposive sampling. Instruments included the Coworker Social Support Scale (32 items, α = 0.910), Gratitude Questionnaire (adapted GQ-6, 29 items), and Satisfaction with Life Scale (SWLS, α = 0.921). Data analysis utilized multiple regression with IBM SPSS 26.0, following tests for normality, linearity, multicollinearity, and heteroscedasticity. Results indicate a significant simultaneous relationship between coworker social support and gratitude with life satisfaction (R = 0.759, R² = 0.576, F = 67.183, p < 0.001), contributing 57.6% to variance, with the remainder influenced by other factors. Individually, coworker social support shows a positive significant correlation (r = 0.089, p = 0.002, effective contribution 3.79%), while gratitude exhibits a stronger link (r = 0.713, p < 0.001, effective contribution 53.83%). The regression equation is Y = 15.199 + 0.093X₁ + 0.657X₂. Findings underscore the protective roles of social support and gratitude in enhancing life satisfaction amid occupational hardships. Practically, schools and local education authorities may utilize these findings by designing collegial work-climate strengthening programs, peer-support forums, structured mentoring systems, and gratitude-based reflective activities integrated into teacher development initiatives. Such programs may serve as preventive strategies to promote teachers’ psychological well-being. Future research is encouraged to incorporate additional variables, such as work-life balance, using mixed methods approaches.